Effects of ractopamine hydrochloride supplementation on feeding behavior, growth performance, and carcass characteristics of finishing steers(,) - Trotta, Ronald J (Transl Anim Sci, 2019)
Ractopamine hydrochloride (RAC) is a β-adrenergic agonist that functions as a repartitioning agent to improve muscling in feedlot cattle. Many studies have investigated the effects of RAC on growth performance and carcass characteristics; however, there is minimal information about the influence of RAC on feeding behavior. Sixty-nine steers (body weight [BW] = 364 ± 3.9 kg) predominately of Angus and Simmental breeding were subjected to a 126-d (n = 46) or 154-d (n = 23) feeding period and randomly assigned to one of two treatment groups: supplementation to provide 0 (CON; n = 34) or 267 ± 4.9 mg/d of RAC (n = 35). Ractopamine was provided as Optaflexx 45 at 0.024% of the diet (dry matter [DM] basis; Elanco Animal Health, Greenfield, IN). Dietary treatments were fed the final 42 d in the feed yard (treatment period). Feeding behavior and growth performance were measured using radio frequency identification tags and the Insentec feeding system. Following the final day of treatment, steers were slaughtered and carcass measurements were recorded. Data were analyzed using MIXED models in SAS. There were no differences in BW, average daily gain (ADG), DM intake (DMI), gain:feed ratio (G:F), or feeding behavior during the pretreatment period (P > 0.44). Ractopamine supplementation increased G:F during the treatment period (P = 0.02) and during the total period (P = 0.03) and tended to increase ADG during the treatment and total period (P ≤ 0.08). DMI was not affected during the treatment or total period (P > 0.67). Eating time per visit, per meal, and per day were decreased (P < 0.02) in steers supplemented with RAC during the treatment period. DMI per minute was increased (P = 0.02) in steers supplemented with RAC. Hot carcass weight, dressing percentage, and 12th rib fat were not influenced by RAC supplementation. Ractopamine supplementation decreased marbling (P = 0.008) and kidney, pelvic, and heart percentage (P = 0.04) and increased longissimus muscle area (P = 0.01). These data demonstrate that RAC supplementation for 42 d improves feed efficiency, increases the rate of DMI without altering DMI, and increases muscling in finishing cattle.